The Influence of Leadership and Work Environment on Employee Performance at PT. Suksesindo Pratama in Jakarta - Mukhlis Catio (Program Pascasarjana Universitas Negeri Makassar, 2020)
To achieve the goals of the company, then a leader must apply a leadership style to manage his subordinates because a leader will greatly influence the success of the organization in achieving its objectives. This study aims to determine the effect of leadership and work environment on employee performance at PT. Suksesindo Pratama in Jakarta. The method used was explanatory research with a sample of 60 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study leadership have a significant effect on employee performance by 45.5%, hypothesis testing obtained significance 0,000 <0.05. The work environment has a significant effect on employee performance by 24.4%, the hypothesis test obtained a significance of 0,000 <0.05. Simultaneous leadership and work environment significantly influence employee performance by 50.7%, hypothesis testing obtained significance 0,000 <0.05